New photonic components for quantum information science - Politi,A; Matthews,JCF; Laing,A; Peruzzo,A; Poulios,K; Meinecke,J; Bonneau,D; Shadbolt,P; Kalasuwan,P; Zhou,XQ; Verde,MR; Lobino,M; et al. (2011)
New photonic components are required to exploit the integrated architecture for Quantum Information science. We demonstrate quantum interference in MMI couplers and twoparticle quantum walks in coupled waveguides, showing unique quantum behaviour. © OSA/ANIC/IPR/Sensors/SL/SOF/SPPCom/2011.